2015
DOI: 10.1209/0295-5075/111/18005
|View full text |Cite
|
Sign up to set email alerts
|

Modification of surface chemistry by lattice Sn doping in BiFeO 3 nanofibers

Abstract: Results on X-ray near edge structure (XANES) study on Sn-doped BiFeO3 (BFO) nanofibers with varying Sn concentrations of 1%, 3%, and 5% are reported. The results indicate that the oxidation state of Sn ions in the BFO structure is +4. In addition, we observe a bismuth peak (Bi M1) at 4000 eV in the XANES spectrum, suggesting the diffusion of Bi ions onto the surface of BFO nanostructure. The diffusion is attributed to the charge compensation between donor electrons from the Sn atoms and Bi vacancies. These fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…It has been reported that the doping of Gd 3+ at A-site onto BFO shows enhanced photocatalytic degradation of Rhodamine B due to ferromagnetic behavior 43 . Additionally, the effects of Sn 4+ doping on the morphology and electromagnetic properties of BFO have been studied 44 45 .…”
mentioning
confidence: 99%
“…It has been reported that the doping of Gd 3+ at A-site onto BFO shows enhanced photocatalytic degradation of Rhodamine B due to ferromagnetic behavior 43 . Additionally, the effects of Sn 4+ doping on the morphology and electromagnetic properties of BFO have been studied 44 45 .…”
mentioning
confidence: 99%
“…Figure 9 illustrates the basic mechanism of dye degradation under visible light, as well as in the dark (absence of light). In the presence of light, electrons travels to the conduction band of BGFSO nanoparticles, from the valence band and the donor shallow energy levels, created below the bottom of conduction band due to the doping of Sn [10]. GNPs lower the recombination rate of electron-hole charge carriers by acting as trapping site of electron [14].…”
Section: Dye Degradation Mechanismmentioning
confidence: 99%
“…Perovskite structures have gained great attention, due to their fascinating physical characteristics, and initiated many useful applications in different technological areas [7][8][9]. Perovskites are materials having chemical formula ABO 3 [10] where, A is usually a bigger cation than B cation and O is oxygen (anionic specie). The key features of perovskite materials include simple and easy fabrication, huge solar adsorption, less non-radiative charge carrier recombination, high mobility of carriers for cell architectures and capitalization of dye sensitized photovoltaic cells [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the poor magnetization performance of bulk BFO limits its practical applications [8,9], As is known to all, the lone electron pairs of Bi 3+ lead to the ferroelectric properties of BFO, whereas G-type antiferromagnetic is the result of the ordering of Fe 3+ spins with a complicated long-period modulation about 62 nm [10,11]. Therefore, the ferromagnetism can be enhanced by destroying the spiral spin structure.…”
Section: Introductionmentioning
confidence: 99%